Determination of N2O reduction to N2 from manure-amended soil based on isotopocule mapping and acetylene inhibition. (1st January 2021) - Lin, Wei; Ding, Junjun; Li, Yujia; Zheng, Qian; Zhuang, Shan; Zhang, Dongdong; Zhou, Wanlai; Qi, Zhiyong; Li, Yuzhong
Abstract: The quantification of N2 O reduction during denitrification is crucial to take measures reducing N2 O emissions from arable soils. The analysis of site specific N2 O isotopic composition may help to quantify the pathway of N2 O reduction to N2 during denitrification process. In manure-amended soil (chicken manure, cow manure and sheep manure), N2 O reduction was evaluated by examining the N2 O emissions in the presence of acetylene (C2 H2 ) and by analyzing the N2 O isotopocule deltas. The results indicated that the three manures had no significant differences for the N2 O emission rates and N2 O isotopocule deltas. The extent of N2 O reduction to N2 was 81–84% using the mapping of Δδ 18 O(N2 O-H2 O/N2 O-NO3 - ) (different value of δ 18 O between the N2 O and H2 O or NO3 − ) vs. SP ( 15 N site preference in N2 O) and approximately 76% using C2 H2 (10% v/v) inhibition method under 60% WFPS (water–filled pore space). Moreover, complete N2 O reduction held η 18 OR and SPR (net isotopocule effect of N2 O reduction to N2 ) values of −13.6‰ and −6.7‰, respectively. It was also found that oxygen exchange between N2 O and soil water was approximately 92%. In summary, the mapping of Δδ 18 O(N2 O-H2 O/N2 O-NO3 - ) vs. SP was very useful to distinguish the production and consumption pathways of N2 O during denitrification. The extent of N2 O reduction was underestimated by the C2 H2 method. These results provide guidance in correcting the acetylene effect, which is important in evaluating the impact of manure on the N2 O reduction. Highlights: The mapping of Δδ 18 O(N2 O-H2 O/N2 O-NO3 - ) vs. SP was more accurate for N2 O source partitioning. The isotopocule effect of Oxygen and SP during N2 O reduction were −13.6‰ and −6.7‰, respectively. Acetylene method underestimated the N2 O reduction extent from manure-amended soil under 60% WFPS. The extent of oxygen exchange between N2 O and soil water was approximately 92%.